A etnomatemática na educação do campo, em contextos indígena e ribeirinho, seus processos cognitivos e implicações à formação de professores - Costa, Lucélida de Fátima Maia da (2012)
The search for comprehension about educational relations on the country education context is several times complex and requires knowledge of different coexistent realities, how they built, rebuilt and influences the ways of teaching and learning from subjects who live in the country. In this dissertation are presented the results of a qualitative research which goal is to comprehend in what measurement the Ethno Mathematics and its cognitive processes constitute implications for the teachers’ training from the country schools. The investigation was developed into four distinct realities on the country education context, one concerning a continuous teachers’ training of the by the river inhabitants in the Parintins district, two concerning indigenous teachers’ graduation (the reality of non-indigenous developer teacher and the indigenous teacher in training), and one involving indigenous students, the latter takes place in Alto Solimões Region. For achieving data the participant observation was used next to the teachers of the by the river inhabitants communities, questionnaires were applied for developer indigenous teachers and the socio cultural direct observation like the production of manioc flour and wooden sculptures. The data obtained were analyzed by the light of the Ethno Mathematics, of mobilization of Cognitive Processes and Cognitive Education, taking for basis authors like D’Ambrosio (2005), D’Ambrosio (1993), Vygotsky (1995), Pinker (2002), Pinker (2008), Stemberg (2010), Fonseca (2009) and Freire (1981), who indicate the necessity of reflection on the teachers’ training processes, once that, on the country education context is impractable to think about mathematical education with no consider the construction of mathematical thought that occurs in the development of socio cultural activities realized by the subjects in the interactions that realize on their everyday life.